A highly expressed intestinal cysteine protease of Ancylostoma ceylanicum protects vaccinated hamsters from hookworm infection. - Jason B Noon; Erich M Schwarz; Gary R Ostroff; Raffi V Aroian (Public Library of Science (PLoS), 2019)
Background Human hookworms (Necator americanus, Ancylostoma duodenale, and Ancylostoma ceylanicum) are intestinal blood-feeding parasites that infect ~500 million people worldwide and are among the leading causes of iron-deficiency anemia in the developing world. Drugs are useful against hookworm infections, but hookworms rapidly reinfect people, and the parasites can develop drug resistance. Therefore, having a hookworm vaccine would be of tremendous benefit. Methodology/principal findings We investigated the vaccine efficacy in outbred Syrian hamsters of three A. ceylanicum hookworm antigen candidates from two classes of proteins previously identified as promising vaccine candidates. These include two intestinally-enriched, putatively secreted cathepsin B cysteine proteases (AceyCP1, AceyCPL) and one small Kunitz-type protease inhibitor (AceySKPI3). Recombinant proteins were produced in Pichia pastoris, and adsorbed to Alhydrogel. Recombinant AceyCPL (rAceyCPL)/Alhydrogel and rAceySKPI3/Alhydrogel induced high serum immunoglobulin G (IgG) titers in 8/8 vaccinates, but were not protective. rAceyCP1/Alhydrogel induced intermediate serum IgG titers in ~60% of vaccinates in two different trials. rAceyCP1 serum IgG responders had highly significantly decreased hookworm burdens, fecal egg counts and clinical pathology compared to Alhydrogel controls and nonresponders. Protection was highly correlated with rAceyCP1 serum IgG titer. Antisera from rAceyCP1 serum IgG responders, but not nonresponders or rAceyCPL/Alhydrogel vaccinates, significantly reduced adult A. ceylanicum motility in vitro. Furthermore, rAceyCP1 serum IgG responders had canonical Th2-specific recall responses (IL4, IL5, IL13) in splenocytes stimulated ex vivo. Conclusions/significance These findings indicate that rAceyCP1 is a promising vaccine candidate and validates a genomic/transcriptomic approach to human hookworm vaccine discovery.